Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1108/ijoem-10-2020-1288
|View full text |Cite
|
Sign up to set email alerts
|

Oil price volatility and firm profitability: an empirical analysis of Shariah-compliant and non-Shariah-compliant firms

Abstract: PurposeThis study examines the impact of oil price volatility on firm profitability. As Shariah-compliant firms operate under restrictions, the study also explores whether oil price volatility affects Shariah-compliant firms differently from their non-Shariah-compliant counterparts.Design/methodology/approachThe study sample includes all non-financial firms listed on Gulf Cooperation Council stock exchanges from 2005 to 2019. In evaluating the oil price volatility–profitability relationship, static (panel fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…The findings are in line with Bugshan et al (2021) who indicated that the higher-level uncertainty exposes Shariah-compliant firms to higher bankruptcy risks compared to non-Shariah-compliant firms, mainly due to the restrictions imposed on Shariahcompliant firms. The financial structure of Shariah-compliant firms is less dynamic and flexible, especially in relation to external financing options (Bugshan et al, 2021b). Thus, cash reserves play a crucial role in the survival of Shariah-compliant firms.…”
Section: Regression Resultsmentioning
confidence: 99%
“…The findings are in line with Bugshan et al (2021) who indicated that the higher-level uncertainty exposes Shariah-compliant firms to higher bankruptcy risks compared to non-Shariah-compliant firms, mainly due to the restrictions imposed on Shariahcompliant firms. The financial structure of Shariah-compliant firms is less dynamic and flexible, especially in relation to external financing options (Bugshan et al, 2021b). Thus, cash reserves play a crucial role in the survival of Shariah-compliant firms.…”
Section: Regression Resultsmentioning
confidence: 99%
“…Because sharia-compliance businesses have limitations whereas non-compliant businesses do not, the impact of oil price volatility is larger on sharia-compliant businesses than on nonsharia compliant businesses (Bugshan et al, 2021). As a result, additional Islam-compliant instruments should be developed to compete with existing instruments in order to help sharia-compliant firms manage uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Sharia-compliant firms are subject to constraints whereas non-shariah compliant firms are not, therefore the impact of oil price volatility is greater on sharia-compliant firms than on non-shariah compliant firms. As a result, non-sharia compliant firms are better equipped to deal with short-term uncertainty (Bugshan et al, 2021).…”
Section: Sharia-compliant Organizationmentioning
confidence: 99%
“…The effect of the oil price on a business and a nation is equivalent for a variety of businesses and alliances. Using panel fixed effects and the generalized method of moments, Bugshan et al (2021) conducted a study between 2005 and 2019 on oil price volatility and the corporate profitability of Shariah based and non-Shariah based businesses. It was found that during periods of significant oil price fluctuations, Shariah-compliant firms were more likely to fail than non-compliant businesses, according to the research.…”
Section: Literature Reviewmentioning
confidence: 99%